The Middle Ground: The Politics of the Mix-Blood Leader Alexander McGillivray - Villanueva, Christian (The Toro Historical Review, 2025)
This paper explores the indigenous politics of the Creeks under Alexander McGillivray through the perspective of the middle ground a concept explored by Richard White in his analysis of the Great Lakes Region. The paper will explore a different region and indigenous group which illustrates the political influence mixed-heritage Native Americans had in era, specifically Alexander McGillivray. In this negotiation, he was able to secure the Treaty of Pensacola and the Treaty of New York (1790) which would protect the Creek land from potential infringements. The paper will explore the middle ground as a concept, the racial politics of the era, the rise to power of McGillivray, and finally the accomplishment he was able to secure to protect the Creek Nation. It will show how the mixed- heritage of McGillivray was a contributing factor, that would help the Creek Nation.